Rethinking the “Hamidian massacres”: the issue of the precedent - Boris Adjemian; Mikaël Nichanian (Études Arméniennes Contemporaines, 2018)
This text is an introduction to the theme issue of Études arméniennes contemporaines on “The Massacres of the Hamidian Period: Global Narratives and Local Approaches”.